Drug abuse: neurobiological and terapeutic generalities - Velásquez-Martínez, María Carolina; Ortiz, Jose (Actualidades en Psicología, 2014)
Drug abuse is an illness characterized by the urge to obtain and consume a given substance independently of the negative consequences. There are biological, social and psychological factors that predispose an individual to abuse drugs. Adolescents are most vulnerable because their brain has not fully matured yet and there are strong social and psychological pressures. Thus, prevention is most effective at this age. Most abused drugs target the brain's mesocorticolimbic system. Dopamine and glutamate play a major role in this circuit that normally mediates motivated behaviors. It is thought that abused substances modify this circuit using mechanisms similar to normal learning resulting in dysfunctional learning. Such changes are very long lasting and can be evoked by events reminiscent of the drug abuse, in the absence of the drug. A multidisciplinary approach is needed because drug abuse has biological, social and psychological components. Cognitive and behavioral therapies are often paired with pharmacological agents that address specific drug withdrawal and abstinence symptoms.